A new approach for affinity-based purification of horseradish peroxidase - Almaz, Züleyha; Öztekin, Aykut; Abul, Nurgül; Gerni, Serpil; Erel, Deniz; Koçak, Seyma Mehtap; Şengül, Mehmet Emin (Wiley, 2021)
We have developed efficient procedure for isolation of horseradish peroxidase (HRP) using aminobenzohydrazide-based affinity chromatography. Sepharose 4B-bounded aminobenzohydrazides are suitable for long-term use and large-scale purification. In this study, 26 aminobenzohydrazide derivatives were synthesized, characterized and defined as new HRP inhibitors. In addition, detailed inhibition effects of these molecules on HRP enzyme were investigated. Affinity matrix was formed by bonding aminobenzohydrazides, which exhibited inhibitory activity to sepharose-4B-l-tyrosine. HRP was isolated from crude homogenate in single step and purification factors were recorded as 1,151-fold (recovery of 8.5%) with 4-amino 3-bromo benzohydrazide and as 166.16-fold (recovery of 16.67 %) with 3-amino 4-chloro benzohydrazide.
OZTEKIN, Aykut/0000-0003-1418-179X; Almaz, Zuleyha/0000-0002-4532-4311
Keywords: affinity purification; benzohydrazide; horseradish peroxidase